Religiusitas sebagai Sumber Ordinary Magic untuk Membangun Resiliensi dan Relevansinya pada Layanan Psikoedukasi di Sekolah - Achmad Miftachul 'Ilmi; Muslihati Muslihati; Agung Minto Wahyu; Nur Mega Aris Saputra; Hawiki Renalia; Elita Elidayanti; Shania Dea Menany Soputan (State Islamic University (UIN) Salatiga, 2025)
COVID-19 survivors with chronic illnesses face layered physical, emotional, and spiritual pressures. In a religious society like Indonesia, religiosity plays a vital role in fostering long-term psychological resilience. This study aims to (1) explore resilience patterns based on Ann S. Masten’s Ordinary Magic theory, (2) analyze the role of religiosity in activating adaptive strengths during grief from chronic illness, and (3) examine its relevance for developing school-based psychoeducational services. Using a qualitative phenomenological approach, data were collected purposively from six survivors with comorbidities and two supporting informants. In-depth interviews and observations were analyzed thematically using MAXQDA. Findings revealed four key resilience patterns: stress resistance, recovery, normalization, and posttraumatic growth, all significantly shaped by religiosity. Practices such as prayer, spiritual reflection, and finding transcendental meaning helped individuals manage emotions, sustain hope, and build inner strength. These insights highlight the potential for integrating spiritual values into psychoeducational programs to support student resilience. Further research is encouraged to develop religiosity-based preventive interventions tailored to educational settings.